Pemanfaatan Software Moodle untuk Membangun Sistem Pembelajaran On-Line Bagi Guru MTs Dan MA Muhammadiyah Kota Medan - Susiana Susiana; Said Iskandar Al Idrus; Chairunisah Chairunisah (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2015)
The effective learning requires a good learning system and learning resources which can be obtained easily, not place or time limited. Actually, the Advances of technology today can support the creation of learning resources, but the use of technology  by schools in Medan is still not maximal, including MTs Muhammadiyah 15 dan MA Muhammadiyah 1 Medan. One of the reasons is the teachers did not have skill to manage an e-learning which it has to involve teachers and students at once. Moodle is a learning management system which is most popular today.This dedication activity aims to provide knowledge and skill for the teachers to use moodle as one of the ways to implement learning process. There are two phases of this event:1) workshop; introduction of e-learning and moodle, 2) accompaniment; Participants had guided and assisted in designing a learning device that is packed  in e –learning form. In general, the event had implemented successfully. Outcomes of this activity are : a)learning device such as syllabus , teaching materials  and exam questions, b)learningdevices are packed on-line at www.mam1medan.sch.id and www.mts15muhammadiyah.sch.id, c ) recording a video on how to use e -learning from the web that has been made.